Highly consistent temporal lobe interictal spike networks revealed from foramen ovale electrodes. Issue 9 (September 2021) - Maharathi, Biswajit; Patton, James; Serafini, Anna; Slavin, Konstantin; Loeb, Jeffrey A.
Highlights: Interictal spike network is highly reproducible across time and frequency bands in temporal lobe patients with foramen ovale electrodes. Interictal spike networks are both bilateral and unilateral, where they are closely related to seizure onset zones and structural lesions. A small fraction of mesial temporal Spikes are associated with cortical spikes but without a clear pattern of propagation. Abstract: Objective: A major challenge that limits understanding and treatment of epileptic events from mesial temporal structures comes from our inability to detect and map interictal networks reproducibly using scalp electrodes. Here, we developed a novel approach to map interictal spike networks and demonstrate their relationships to seizure onset and lesions in patients with foramen ovale electrode implantations. Methods: We applied the direct Directed Transfer Function to reveal interictal spike propagation from bilateral foramen ovale electrodes on 10 consecutive patients and co-registered spatially with both seizure onset zones and temporal lobe lesions. Results: Highly reproducible, yet unique interictal spike networks were seen for each patient (correlation: 0.93 ± 0.13). Interictal spikes spread in both anterior and posterior directions within each temporal lobe, often reverberating between sites. Spikes propagated to the opposite temporal lobe predominantly through posterior pathways. Patients with structural lesions (N = 4), including tumors and sclerosis, developed reproducible spike networks adjacent to their lesions that were highly lateralized compared to patients without lesions. Only 5% of mesial temporal lobe spikes were time-locked with scalp electrode spikes. Our preliminary observation on two lesional patients suggested that along with lesion location, Interictal spike networks also partially co-registered with seizure onset zones suggesting interrelationship between seizure onset and a subset of spike networks. Conclusions: This is the first demonstration of patient-specific, reproducible interictal spike networks in mesial temporal structures that are closely linked to both temporal lobe lesions and seizure onset zones. Significance: Interictal spike connectivity is a novel approach to map epileptic networks that could help advance invasive and non-invasive epilepsy treatments.